Telegram - Elger, William
032-0096-001 POST OFFICE TELEGRAM Prefix. Time handed in. Office of Origin and Service Instructions. Words. 105 11.31 GLASGOW T 29 DEWSON TRADUNIC SOWEST LONDON = REFERENCE LETTER FEBRUARY 7 TH ABERDEEN TRADES COUNCIL FOUR TONS FOODSTUFFS YOUR GUIDANCE OF FEBRUARY 10 TH RECEIVED TOO LATE CAN YOU SUGGEST ANY OTHER SHIPMENT = ELGER + telephoned 17/2/39 5.40 pm: Boat Wednesday 22nd ("Latino") address Jose Castro F.I.S. Bon Repos Valencia (at his request). CT 7 TH 10 TH + For free repetition of doubtful words telephone "TELEGRAMS ENQUIRY" or call, with this form at office of delivery. Other enquiries should be accompanied by this form and, if possible, the envelope. 292/946/32/96